Transcriptional Activity of PGC-1α and NT-PGC-1α Is Differentially Regulated by Twist-1 in Brown Fat Metabolism - Hee-Jin Jun; Thomas W. Gettys; Ji Suk Chang (PPAR Research)
Brown fat expresses two PGC-1α isoforms (PGC-1α and NT-PGC-1α) and both play a central role in the regulation of cellular energy metabolism and adaptive thermogenesis by interacting with a wide range of transcription factors including PPARγ, PPARα, ERRα, and NRF1. PGC-1α consists of 797 amino acids, whereas alternative splicing of the PGC-1α gene produces a shorter protein called NT-PGC-1α (aa 1–270). We report in this paper that transcriptional activity of PGC-1α and NT-PGC-1α is differently affected by the transcriptional regulator, Twist-1. Twist-1 suppresses PGC-1α but not NT-PGC-1α. The inhibition of PGC-1α activity by Twist-1 is mediated by direct interaction through the C-terminal region of PGC-1α (aa 353–797). Thus, the absence of the corresponding C-terminal domain in NT-PGC-1α allows NT-PGC-1α to be free from Twist-1-mediated inhibition. Overexpression of Twist-1 in brown adipocytes suppresses transcription of a subset of PGC-1α-target genes involved in mitochondrial fatty acid oxidation and uncoupling (CPT1β, UCP1, and ERRα). In contrast, NT-PGC-1α-mediated induction of these genes is unaffected by Twist-1. These findings show that differences in inhibitory protein-protein interactions of PGC-1α and NT-PGC-1α with Twist-1 lead to differential regulation of their function by Twist-1.